Probematika Agama dan Negara: Perspektif Sejarah - Darajat, Zakiya (Fakultas Adab and Humaniora, Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2019)
Discourse on the relationship between religion and state seems to be a discourse that never ends to be discussed. The emergence of a statement of President Jokowi on March 24, 2017 which discourse the separation between religion and politics immediately launched a public reaction. Some agreed, but many also criticized. For those who agree with the statement Jokowi reasoned that religion is often used as a politician tool that has the potential to divide the nation. But for those who reject Jokowi's statements argue that the separation of religion from the state is the same as denying the basis and philosophy of the state which has historically been extracted from the values of the religiosity of the Indonesian nation itself. Using historical, sociological and political approaches, this article intends to analyze how discourses on the relation between religion and state taking place in Indonesia in the historical perspective, as well as the problems it causes. This paper proves that although experiencing ups and downs, judging from the historical geneologi, the life of the nation and the state of Indonesia can not be separated from the values of religiosity. Both are always symbiotic mutualism. Putting the Godhead of the One Supreme God as the first principle in Pancasila, is in fact an acknowledgment of the importance of religious values in the life of the nation and the state.—Diskursus tentang relasi antara agama dan negara seolah menjadi wacana yang tak pernah usai untuk dibahas. Munculnya statemen Presiden Jokowi pada 24 Maret 2017 yang mewacanakan pemisahan antara agama dan politik segera menyeruakkan reaksi publik. Ada yang mengiyakan, tapi banyak juga yang mengecam. Bagi yang setuju dengan statemen Jokowi beralasan bahwa agama sering kali dijadikan sebagai alat politisasi yang berpotensi memecah belah bangsa. Namun bagi mereka yang menolak statemen Jokowi berargumentasi bahwa upaya pemisahan agama dari negara sama halnya dengan mengingkari dasar dan falsafah negara yang secara historis justru digali dari nilai-nilai religiusitas bangsa Indonesia itu sendiri. Dengan menggunakan pendekatan sejarah, sosiologis dan politik, artikel ini bermaksud menganalisis bagaimana diskursus tentang relasi antara agama dan negara yang terjadi di Indonesia dalam perspektif sejarah, serta problematika yang ditimbulkannya. Tulisan ini membuktikan bahwa meskipun mengalami pasang surut, dilihat dari geneologi kesejarahan, kehidupan berbangsa dan bernegara Indonesia tidak bisa dilepaskan dari nilai-nilai religiusitas. Keduanya senantiasa bersimbiosis mutualisme. Diletakkannya Sila Ketuhanan Yang Maha Esa sebagai sila pertama dalam Pancasila, sejatinya merupakan sebuah pengakuan akan pentingnya nilai-nilai religiusitas dalam kehidupan berbangsa dan bernegara.